Fabrication of a hybrid phase TiO2/g-C3N4 heterojunction composite with enhanced adsorption and photocatalytic degradation of MB under visible light. (11th April 2023) - Liu, Shuanghui; Wang, Changle; Song, Yao; Yan, Binglin; Ai, Bing; Pan, Kefeng; Zhang, Lipeng
Abstract : Excellent MB adsorption and degradation capacity of hybrid phase TiO2 /g-C3 N4 photocatalysts based on surface polarization and S-scheme charge transfer. Abstract : The heterojunction structure of semiconductor photocatalysts is significant for making full use of their capabilities for organic molecules and dye degradation. In this paper, we present a heterogeneous junction composite fabricated with hybrid phase TiO2 and g-C3 N4 for methylene blue (MB) removal through adsorption and photocatalytic degradation. The heterogeneous junction system was prepared by hydrothermal treatment with a subsequent pyrolysis process. The variation of the proportion and lattice structure of hybrid phase TiO2 in the synthesized catalysts was analyzed by refinement. Adsorption experiments showed that the maximum adsorption capacity of TiO2 /g-C3 N4 (1 : 10) was 1667 mg g −1, which was 45.97 times and 63.78 times higher than that of TiO2 and g-C3 N4, respectively. In the photodegradation process, the TiO2 /g-C3 N4 (1 : 10) photocatalyst shows a removal rate of MB of 100 mg L −1, which was as high as 96.262%, significantly higher than that of pure TiO2 and g-C3 N4 . Brunner–Emmett–Teller (BET) measurements and Fourier transform infrared spectroscopy (FTIR) showed that the adsorption of MB onto TiO2 /g-C3 N4 (1 : 10) was chemical adsorption, and ˙OH, which acts as an active substance, was found to play a major role in the photocatalytic degradation process. Overall, the developed hybrid phase TiO2 /g-C3 N4 heterojunction composite may be beneficial for the treatment of water pollution.